Association of reovirus outer capsid proteins sigma 3 and mu 1 causes a conformational change that renders sigma 3 protease sensitive. - Shepard, D A (1995)
Association of the reovirus proteins sigma 3 and mu 1 influences viral entry, initiation of outer capsid assembly, and modulation of the effect of sigma 3 on cellular translation. In this study, we have addressed whether structural changes occur in sigma 3 as a result of its interaction with mu 1. Using differences in protease sensitivity to detect conformationally distinct forms of sigma 3, we showed that association of sigma 3 with mu 1 caused a conformational change in sigma 3 that converted it from a protease-resistant to a protease-sensitive structure and occurred posttranslationally. The effect of mu 1 on the structure of sigma 3 was stoichiometric. Our results are consistent with a model in which sigma 3's association with mu 1 shifts its function from translational control to assembly of an outer capsid in which sigma 3 is folded into the protease-sensitive conformation that is required for its cleavage during the next round of infection.